2019
DOI: 10.1155/2019/5814265
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Techno-Economic Analysis of Solar-Geothermal Organic Rankine Cycle Technology for Power Generation in Nepal

Abstract: The current research study focuses on the feasibility of stand-alone hybrid solar-geothermal organic Rankine cycle (ORC) technology for power generation from hot springs of Bhurung Tatopani, Myagdi, Nepal. For the study, the temperature of the hot spring was measured on the particular site of the heat source of the hot spring. The measured temperature could be used for operating the ORC system. Temperature of hot spring can also further be increased by adopting the solar collector for rising the temperature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Among the sources of renewable energy, geothermal has the potential to resolve the energy demand in countries with geothermal reserves. Geothermal energy provides innumerable benefits over other sources of energy since is not affected by climatic variability [ 1 , 2 ]. Considering Africa, Kenya is the leading in geothermal energy with an installed capacity of 863 MW.…”
Section: Introductionmentioning
confidence: 99%
“…Among the sources of renewable energy, geothermal has the potential to resolve the energy demand in countries with geothermal reserves. Geothermal energy provides innumerable benefits over other sources of energy since is not affected by climatic variability [ 1 , 2 ]. Considering Africa, Kenya is the leading in geothermal energy with an installed capacity of 863 MW.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cycle enhancements should be given for turbines, evaporators, condensers and hot water supply respectively. Baral [15] made a techno-economic study of a solar-geothermal hybrid ORC cycle by using R134a and R245fa as organic fluids for system performance, and found that the thermal efficiency of the system changes with the temperature of the heat source : the higher the temperature of the hot source, the greater the thermal efficiency of the cycle.…”
Section: Introductionmentioning
confidence: 99%
“…These media are commonly used in the direct utilization of geothermal energy for agricultural, swimming pool, and greenhouse purposes [12]. However, the indirect utilization of geothermal energy is implemented for electricity power production [13], like Chena hot springs commercial power plant that generates 210 kW of electricity power with 8.2% thermal efficiency [14]. Thermal springs with temperatures between 21 to 149°C exist in more than 80 countries [15].…”
Section: Introductionmentioning
confidence: 99%